1999
DOI: 10.1046/j.1365-313x.1999.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

A tomato homeobox gene (HD‐Zip) is involved in limiting the spread of programmed cell death

Abstract: Summary Antisense suppression in transgenic tomato plants of H52, a gene encoding a new homeodomain protein of the HD‐Zip class, produces a conditional lethal phenotype. The transgenic lines that survive exhibit spontaneous misregulation of cell death control in leaves, which, once initiated, propagates and engulfs the entire leaf. Activation of defence genes, over‐accumulation of ethylene and conjugated salicylic acid, and growth reduction of virulent pathogens also occurs in these plants. In wild‐type plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 39 publications
0
41
0
3
Order By: Relevance
“…The latter is characterized by an additional Leu zipper motif adjacent to the homeodomain that facilitates homodimerization and heterodimerization of the transcriptional regulators. Functional characterization of some members of the homeobox family supports a role for some of them as key regulators of hormone signaling (Himmelbach et al, 2002), adaptive responses to environmental cues (Steindler et al, 1999;Zhu et al, 2004), and pathogen-derived signaling processes (Mayda et al, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…The latter is characterized by an additional Leu zipper motif adjacent to the homeodomain that facilitates homodimerization and heterodimerization of the transcriptional regulators. Functional characterization of some members of the homeobox family supports a role for some of them as key regulators of hormone signaling (Himmelbach et al, 2002), adaptive responses to environmental cues (Steindler et al, 1999;Zhu et al, 2004), and pathogen-derived signaling processes (Mayda et al, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…SlHZ25 (H52) was involved in cellular protection by limiting spread of programmed cell death in plants, which showed a close relationship with ATHB5, -6, and -16 of class I in clade β2. 19,45) VA-HOX1 is one of tomato HD-Zip I protein in η clade protein whose expression increased in sepals after cold treatment, its regulation induced by cool temperatures was independent of ethylene. 46) LeHB-1 of tomato HDZip I gene in β2 clade is not only involved in the control of ripening but also plays a critical role in floral organogenesis.…”
Section: Phylogenetic Classification and Structural Analysis Of Slhz mentioning
confidence: 99%
“…CfHNNI1 may function as a cytoplasmic bZIP transcription factor, either directly activating HR and defence signalling through the regulation of downstream plant gene expression, or activating the expression of an elicitor gene of plant origin thereby resulting in the accumulation of active plant elicitor, which then initiates downstream HR signalling. In this context it is noteworthy that H52, a tomato transcription factor containing a leucine-zipper domain, is involved in regulation of programmed cell death (Mayda et al 1999), inferring that the bZIP transcription factor may play a direct role in the regulation of HR and resistance. Additionally, we previously found that amino acids conserved in these domains of bZIP transcription factors are essential for the full function of CfHNNI1 (Cai 2004).…”
Section: Discussionmentioning
confidence: 99%